Measurement of the differential cross section and charge asymmetry for inclusive pp -> W-+/- + X production at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
The differential cross section and charge asymmetry for inclusive pp -> W-+/- + X -> mu(+/-)nu + X production at root s = 8 TeV are measured as a function of muon pseudorapidity. The data sample corresponds to an integrated luminosity of 18.8 fb(-1) recorded with the CMS detector at the LHC. These results provide important constraints on the parton distribution functions of the proton in the range of the Bjorken scaling variable x from 10(-3) to 10(-1).
Keywords: 3-LOOP SPLITTING FUNCTIONS; PARTON DISTRIBUTIONS; QCD; SCATTERING; DENSITIES; EVOLUTION